Exchange rate volatility and growth in small open economies at the EMU periphery - Gunther Schnabl (European Central Bank (ECB), 2007)
Since the introduction of the euro in January 1999, exchange rate stability at the periphery of the euro area is growing. The paper investigates the impact of exchange rate stability on growth for a sample of 41 mostly small open economies at the EMU periphery. It identifies international trade, international capital flows and macroeconomic stability as important transmission channels from exchange rate stability to more growth. It is argued that fixed exchange rates provide a more stable framework for the adjustment of asset and labour markets of countries in the economic catchup process thereby accelerating growth. Panel estimations reveal a robust negative relationship between exchange rate volatility and growth for countries in the economic catch-up process with open capital accounts.
Keywords: F43; F31; E42; 330; EMU Periphery; Exchange Rate Regimes; Exchange rate volatility; Growth; international role of the euro; Wechselkurs; Volatilität; Euro; Internationales Währungssystem; Eurozone; Periphere Region; Kleine offene Volkswirtschaft; Nordafrika; Westasien; Osteuropa; GUS-Staaten